Digital Networking for School Reform: The Online Grassroots Efforts of Parent and Teacher Activists - Heron-Hruby, Alison; Landon-Hays, Melanie; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Presenting school reform grassroots activists - teachers, parents, and organizers alike - in their own words, the editors document the newly emerged role of digital networks of activists in school reform and analyze their efforts as acts of critical literacy.
Keywords: Science; Science; Science, general